Assessment of discordance of treatment satisfaction between patients with rheumatoid arthritis in low disease activity or in remission and their treating physicians: A cross-sectional survey. Issue 2 (4th March 2021) - Kaneko, Yuko; Sato, Masayo; Cai, Zhihong; Sato, Minako
Abstract: Objectives: To assess discordance in overall treatment satisfaction between patients with rheumatoid arthritis (RA) and their physicians. Methods: This was a multicenter, cross-sectional, observational study of patients with RA (in low disease activity or remission) and their board-certified treating physicians in Japan; 202 patient–physician pairs were analyzed. Treatment satisfaction and perceptions were assessed using a structured questionnaire. Results: Using a two-level ('satisfied' or 'unsatisfied') assessment of satisfaction, 195 patients (96.5%) and 190 physicians (94.1%) answered 'satisfied' with a high level of concordance (184 pairs, 91.1%). Using a four-level assessment, the ratio of 'satisfied' to 'somewhat satisfied' was higher in patients (66.3%/30.2%) than physicians (43.6%/50.5%). Satisfaction with treatment outcomes (e.g. joint conditions, subjective symptoms) was generally high in patients and physicians; relatively less satisfaction was reported for medication cost, especially among patients. Shared treatment decision-making was reported in ≥96% of patient–physician pairs. The most common 'most important' treatment target differed between patients ('Have a social life without worrying about RA') and physicians ('Prevent joint damage, deformity, and joint swelling'). Conclusions: Treatment satisfaction and concordance were high between patients in low activity/remission and physicians. Some differences between patients and physicians were reported in satisfaction for specific treatment outcomes and important treatment targets.